CAD in reinforced concrete detailing and structural steelwork proceedings of a conference organized by the Institution of Civil Engineers and held in London on 26 November 1987. (Thomas Telford, 1988)
This work addresses the techniques and products currently available to civil engineers, reviewing their features and highlighting advantages and deficiencies. Case histories of users may be of particular interest.